Targeted next-generation sequencing-based detection of microsatellite instability in colorectal carcinomas. - Yunbeom Lee; Ji Ae Lee; Hye Eun Park; Hyojun Han; Yuhnam Kim; Jeong Mo Bae; Jung Ho Kim; Nam-Yun Cho; Hwang-Phill Kim; Tae-You Kim; Gyeong Hoon Kang (PLoS ONE)
In the present study, we developed a computational method and panel markers to assess microsatellite instability (MSI) using a targeted next-generation sequencing (NGS) platform and compared the performance of our computational method, mSILICO, with that of mSINGS to detect MSI in CRCs. We evaluated 13 CRC cell lines, 84 fresh and 119 formalin-fixed CRC tissues (including 61 MSI-high CRCs and 155 microsatellite-stable CRCs) and tested the classification performance of the two methods on 23, 230, and 3,154 microsatellite markers. For the fresh tissue and cell line samples, mSILICO showed a sensitivity of 100% and a specificity of 100%, regardless of the number of panel markers, whereas for the formalin-fixed tissue samples, mSILICO exhibited a sensitivity of up to 100% and a specificity of up to 100% with three differently sized panels ranging from 23 to 3154. These results were similar to those of mSINGS. With the application of mSILICO, the small panel of 23 markers had a sensitivity of ≥95% and a specificity of 100% in cell lines/fresh tissues and formalin-fixed tissues of CRC. In conclusion, we developed a new computational method and microsatellite marker panels for the determination of MSI that does not require paired normal tissues. A small panel could be integrated into the targeted NGS panel for the concurrent analysis of single nucleotide variations and MSI.